Predictive Value of Monocyte to High-density Lipoprotein Cholesterol Ratio for Nonalcoholic Fatty Liver Disease Merged with Metabolic Syndrome in Community Residents and Associated Factors Assessed Using Multivariate Regression Tree Analysis - Jilin MA, Xueping ZHANG (Zhongguo quanke yixue, 2022)
Background Nonalcoholic fatty liver disease (NAFLD) is rarely detected at early stage, and often found when merged with metabolic disorders. Currently, the predictive value of noninvasive indicators for NAFLD with metabolic syndrome (MS) has been rarely reported. Objective To assess the predictive value of monocyte to high-density lipoprotein cholesterol ratio (MHR) for NAFLD with MS in community residents, and to evaluate the associated factors using multivariate regression tree analysis. Methods From June to December 2020, among 9 812 permanent community residents (>45 years) who underwent physical examination in Songjiang District Sijing Community Health Center, 5 727 eligible individuals were selected, including 4 652 with MS, diabetes, hypertension and dyslipidemia and other metabolic disorders〔1 948 with no NAFLD and MS (controls) , 1 248 with NAFLD (NAFLD cases) , 1 456 with both NAFLD and MS (MAFLD cases) 〕, and 1 075 without metabolic disorders (healthy controls) . General data, anthropometric parameters, blood pressure, biochemical parameters and routine blood test results of all participants were collected. Spearman rank correlation analysis was performed to assess the correlation of MHR and lipid accumulation product (LAP) index with NAFLD and MS. ROC analysis was conducted to analyze the optimal cutoff value of noninvasive indicators〔including neutrophil to lymphocyte ratio (NLR) , platelet to lymphocyte ratio (PLR) , lymphocyte to monocyte ratio (LMR) and MHR〕for NAFLD with MS. Factors associated with the predictive value of above-mentioned noninvasive indicators for NAFLD with MS were identified using multivariate regression tree analysis. Results The prevalence rates for metabolic disorders and NAFLD in this group were 76.61% (7 517/9 812) and 27.59% (2 704/9 812) , respectively. The controls, NAFLD cases, MAFLD cases, and healthy controls had significant differences in female ratio, mean age, BMI, waistline, hipline, waist-to-hip ratio, systolic and diastolic blood pressure, fasting blood glucose, total cholesterol, triacylglycerol, low-density lipoprotein cholesterol, HDL-C, total bilirubin, serum uric acid, ALT, AST, ALT/AST ratio, GGT, eGFR, white blood cell count, neutrophil count, monocyte count, lymphocyte count, platelet count, NLR, PLR, LMR, MHR, alcoholic fatty liver disease to NAFLD index, LAP index, and atherogenic index of plasma, and distribution of waistline and BMI, as well as prevalence of hypertension and dyslipidemia (P<0.01) . Spearman rank correlation analysis showed that, MHR was positively correlated with the grouping (rs=0.342, P<0.001) ; LAP index was also positively correlated with the grouping (rs=0.580, P<0.001) . ROC analysis found that, in the prediction of NAFLD with MS, the AUC of NLR was 0.528〔95%CI (0.511, 0.545) 〕with 74.66% sensitivity, and 31.52% specificity when the optimal cutoff value was chosen as 2.192, that of PLR was 0.581〔95%CI (0.564, 0.598) 〕with 59.82% sensitivity, and 53.95% specificity when the optimal cut-off value was chosen as 115.470, and that of LMR was 0.546〔95%CI (0.529, 0.563) 〕with 51.79% sensitivity, and 56.62% specificity when the optimal cut-off value was chosen as 0.193, and that of MHR was 0.695〔95%CI (0.679, 0.711) 〕with 69.51% sensitivity, and 60.63% specificity when the optimal cut-off value was chosen as 0.292. Multivariate regression tree analysis revealed that sex, BMI, waistline, triacylglycerol, and fasting blood glucose were associated with the predictive value of MHR for NAFLD with MS. Conclusion The value of MHR for predicting NAFLD with MS in physical examinees in the community is relatively high, but it may be significantly influenced by sex, BMI, waistline, triacylglycerol and fasting blood glucose.